Eu(III) complexes as Anion-responsive Luminescent Sensors and PARACEST Agents - Hammell, Jacob (2011)
The Eu(III) complex of (1S,4S,7S,10S)-1,4,7,10-tetrakis(2-hydroxypropyl)-1,4,7,10-tetraazacyclododecane (S-THP) is studied as a sensor for biologically relevant anions. Anion interactions produce changes in the luminescence emission spectrum of the Eu(III) complex, in the (1)H NMR spectrum, and correspondingly, in the PARACEST spectrum of the complex (PARACEST = paramagnetic chemical exchange saturation transfer). Direct excitation spectroscopy and luminescence lifetime studies of Eu(S-THP) give information about the speciation and nature of anion interactions including carbonate, acetate, lactate, citrate, phosphate and methylphosphate at pH 7.2. Data is consistent with the formation of both innersphere and outersphere complexes of Eu(S-THP) with acetate, lactate and carbonate. These anions have weak dissociation constants that range from 19–38 mM. Citrate binding to Eu(S-THP) is predominantly innersphere with a dissociation constant of 17 μM. Luminescence emission peak changes upon addition of anion to Eu(S-THP) show that there are two distinct binding events for phosphate and methylphosphate with dissociation constants of 0.3 mM and 3.0 mM for phosphate and 0.6 mM and 9.8 mM for methyl phosphate. Eu(THPC) contains an appended carbostyril derivative as an antenna to sensitize Eu(III) luminescence. Eu(THPC) binds phosphate and citrate with dissociation constants that are 10-fold less than that of the Eu(S-THP) parent, suggesting that functionalization through a pendent group disrupts the anion binding site. Eu(S-THP) functions as an anion responsive PARACEST agent through exchange of the alcohol protons with bulk water. The alcohol proton resonances of Eu(S-THP) shift downfield in the presence of acetate, lactate, citrate and methylphosphate, giving rise to distinct PARACEST peaks. In contrast, phosphate binds to Eu(S-THP) to suppress the PARACEST alcohol OH peak and carbonate does not markedly change the alcohol peak at 5 mM Eu(S-THP), 15 mM carbonate at pH 6.5 or 7.2. This work shows that the Eu(S-THP) complex has unique selectivity toward binding of biologically relevant anions and that anion binding results in changes in both the luminescence and PARACEST spectra of the complex.